Impact of Environmental Commitment, Environmental Management Accounting and Green Innovation on Firm Performance: An Empirical Investigation - Somjai, Sudawan; Fongtanakit, Ratchada; Laosillapacharoen, Khomsan (International Journal of Energy Economics and Policy, 2020)
The present study aims to analyze the influence of environmental uncertainty on a firm's environmental management accounting. Moreover, the current examination is also motivated to empirically investigate the relationship of environmental commitment, environmental management accounting and green innovation on firm performance. The current study is first in studying the joint impact of the studied variables in analyzing SMEs performance appraisals. In doing so, we applied PLS_SEM and the results of this methodology confirm that all selected variables have a positive and significant impact on environmental performance in except environmental uncertainty. Moreover, the outcomes of the PLS-SEM confirm that environmental commitment has a positive and significant impact on firm performance of multinational firms of Indonesia. Moreover, the results further suggested that environmental uncertainty have a negative and significant impact on firm performance. The results of PLS-SEM also confirm that green innovation and environmental management accounting have significantly and positively impact on firm performance. Technical speaking, the results confirm that green innovation and environmental commitment are the key contributors to enhance the firm performance of Indonesian multinational firms. Keywords: Environmental commitment, Green innovation, Firm performance, Indonesia. JEL Classifications: Q56, L25 DOI: https://doi.org/10.32479/ijeep.9174